Open safety pin ingestion: A pediatric case: Can it be spontaneously eliminated or not? - ERGELEN, RABİA; SÖĞÜTLÜ, YAKUP (MARMARA UNIV, FAC MEDICINE, 2017)
Foreign body ingestion is a common problem in childhood. Sharp objects such as needles, toothpicks or open safety pins can also be ingested. A 13-month-old-boy was admitted to our pediatric emergency department with the suspicion of safety pin ingestion. The boy was taken to a private hospital and an abdominal X-ray was obtained. The open safety pin was seen in the pylorus and he was referred to a university hospital. When he arrived to our pediatric emergency department, an abdominal X-ray was retaken, and an open safety pin was seen in the first part of the duodenum. The patient was hospitalized for observation. After twenty hours, a control X-ray was taken; the open safety pin was seen in the ascending colon. The child was discharged from hospital, and instructions were given to the family for watching his stool closely. The day after, we called the family and learned that the open safety pin was eliminated spontaneously from stool. Infants and children with safety pin ingestion can be closely followed clinically without complication and there will be no need for an endoscopy and/or surgery. An open safety pin ingested small child was reported with the aim to draw attention to safety pin ingestion.
Keywords: Foreign body ingestion; Open safety pin; Blue bead; FOREIGN-BODY INGESTION; CHILDREN; BODIES